Measurement of the WZ and ZZ production cross sections using leptonic final states in 8.6fb -1 of pp̄ collisions - Abazov, V. M.; Abbott, B.; Acharya, B. S.; Adams, M.; Adams, T.; Alexeev, G. D.; Alkhazov, G.; Alton, A.; Alverson, G.; Aoki, M.; Askew, A.; Åsman, B.; et al. (American Physical Society (APS), 2012)
We study the processes pp̄→WZ→ ±ν +- and pp̄→ZZ→ + -νν̄, where =e or μ. Using 8.6fb -1 of integrated luminosity collected by the D0 experiment at the Fermilab Tevatron collider, we measure the WZ production cross section to be 4.50-0.66+0.63pb which is consistent with, but slightly larger than, the prediction of the standard model. The ZZ cross section is measured to be 1.64±0.46pb, in agreement with a prediction of the standard model. Combination with an earlier analysis of the ZZ→ +-+- channel yields a ZZ cross section of 1.44-0.34+0.35pb. © 2012 American Physical Society.